Causal Factors for Conducting Peaceful Settlement between GRP an MILF on Ancestral Domain Aspect 2008 - Fajriyah Nurkhasanah Taufik (UNIDA Gontor, 2016)
This article tries to analyze the dynamic of negotiation processes between Government of Republic of Philippines (GRP) and Moro Islamic Liberation Front (MILF) since 2001 until 2008. It will concern in the negotiation process toward the ancestral domain aspect as the last three major aspects of the Tripoli Agreement on Peace 2001 using literature studies. According to the ripeness theory (Zartman and Faure, 2005), GRP and MILF has been conducting negotiation for 2008 because both conflicting parties have realized the two situations of the Mutually Hurting Stalemate and Mutually Enticing Opportunity. Both conflicting parties has shared the bad experience toward military fighting of Mindanao conflict and realize that by conducting a negotiation they can has expectation on the certain goals for the future. They try to avoid catastrophe situation and gain several benefit from local and international support in the term of politics, social and economic sphere.